Identifikasi Kesulitan Guru Dalam Menyusun Rencana Pelaksanaan Pembelajaran Kurikulum 2013 Di SDN 25 Cakranegara - Luh Ayu Sudarmini; Lalu Hamdian Affandi; Siti Istiningsih (Journal of Science Instruction and Technology, 2021)
One of the responsibilities owned by a teacher before carrying out the learning process in the classroom is that the teacher must draw up a lesson plan is based on the curriculum that has been set. Preparing a plan for the implementation of learning is one of the professional tasks of a teacher. Every teacher has an obligation to draw up a plan for the implementation of learning. This research aims to describe the difficulties faced by teachers in the developed lesson plans at SDN 25 Cakranegara. Data collection techniques are done through interviews and documentation. Data analysis using Milles and Huberman models. The results of this study show that the difficulties experienced by teachers in compiling the RPP Curriculum 2013 include; 1) difficulty in developing components of competency achievement indicators, 2) difficulty in formulating learning goals, 3) difficulty in making and developing assessments. Some of these difficulties are caused by several factors, namely; 1) Lack of understanding that teachers have on the principles of preparing components of the curriculum learning implementation plan 2013, 2) educational background, 3) inadequate availability of time. The solution is done by teachers to overcome these difficulties by asking friends, searching for references over the internet, and utilizing files obtained during training. This research can be concluded that teachers in SDN 25 Cakranegara still have difficulty in compiling curriculum 2013 caused by several factors.